Pengaruh Promosi Online dan Kualitas Pelayanan terhadap Keputusan Pembelian : Survei pada Konsumen Prosperoshoes.id Kota Tasikmalaya - Nur Fitri Yustiani (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine the simultaneous and partial effect of online promotion and service quality on purchasing decisions on Prosperoshoes.id products in the city of Tasikmalaya. The research method used in this study is a quantitative approach with a survey method. The population in this study amounted to 100 respondents. The type of data used in this study is primary data obtained through questionnaire data. The data analysis used is the classical assumption test and multiple regression analysis using SPSS version 25. The results of this study indicate that online promotion and quality simultaneously have a significant effect on purchasing decisions for Prosperoshoes.id products in the city of Tasikmalaya. Online promotion partially has a significant effect on product purchasing decisions at Prosperoshoes.id. Service Quality, partially has a significant effect on product purchasing decisions at Prosperoshoes.id